Preprocedural mouth rinse in COVID-19 era - Chemical and phytotherapeutic approach - Surbhi Gautam; Supreet Shirolkar; Sk Ejaz Ahamed; Sucharita Banerjee; Ashit Kumar Pal; Somen Bagchi (Wolters Kluwer Medknow Publications, 2022)
COVID-19 has impacted the dental services majorly, and there have been some major changes in the dental treatment protocols. As the dental treatment mostly involves the production of aerosols, dentists and dental patients are at high risk of acquiring and transmitting the virus. To reduce the transmission of SARS CoV-2 through aerosols, preprocedural mouth rinse has been recommended. The use of mouthwashes can help in reducing the viral load. The aim of the present review is to discuss different mouthwashes having virucidal action against COVID-19 virus.